The Influence of The Gaming Industry and Esports on The Economy and Society:Advantages and Disadvantages ("Journal "U". Economy. Management. Finance.", 2019)
The digital gaming entertainment industry is expanding every day. At any time, humanity needs some way of spending leisure time. Pastime options have always been in abundance, and they almost all directly depend on the level of technology development. In our time, one of the options was the creation of computer games. The purpose of my article is to study the main indicators of the market of computer games over the past year and identify, based on the analysis of the results of various studies, the positive and negative sides of using them in their spare time. The findings made it clear that the impact of computer games on children and adults is not always negative and even, to some extent, can have a positive impact.
Keywords: economy; society; eSports; video games; influence; money